1982
DOI: 10.2118/8816-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Field Test of Nitrogen WAG Injectivity

Abstract: A one-well field test of nitrogen WAG (water alternating gas) injectivity was conducted to detennine whether a reduction in water injectivity would occur after injection of nitrogen. A 40% reduction was observed immediately after nitrogen injection. Following three short WAG cycles, water injectivity increased to its pretest level with injection of a large volume of water. FEBRUARY 1982 Perforated interval, m (tt) Initial reservoir temperature, °C (OF) Cooled reservoir temperature, °C (OF) Reservoir press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…A 40070 reduction was observed following injection of nitrogen. 6 However, th_e injectivity to gas was considerably higher than the initial water injectivity, such that the total average injection rate during the WAG cycles was not reduced significantly below the waterflood injection rate. Further studies of actual field injection-well capability showed that sufficient excess water injectivity is available to offset water injectivity reductions and that additional injection capacity is available at low cost by installing larger tubing strings in some injection wells.…”
Section: Field Testsmentioning
confidence: 96%
“…A 40070 reduction was observed following injection of nitrogen. 6 However, th_e injectivity to gas was considerably higher than the initial water injectivity, such that the total average injection rate during the WAG cycles was not reduced significantly below the waterflood injection rate. Further studies of actual field injection-well capability showed that sufficient excess water injectivity is available to offset water injectivity reductions and that additional injection capacity is available at low cost by installing larger tubing strings in some injection wells.…”
Section: Field Testsmentioning
confidence: 96%
“…Injectivity loss is one of the frequently reported problems in water-alternating-CO 2 (WAG) flooding. [6][7][8][9][10][11][12][13][14][15][16] We conducted experimental investigations on injectivity loss using four cores during the past three months: the first two cores were Berea cores, the third core was a naturally fractured carbonate reservoir core, and the fourth core was a sandstone reservoir core. The purposes of the experiments were to duplicate situations of injectivity loss in WAG flooding and identify factors affecting the injectivity loss.…”
Section: Preliminary Investigations On Injectivity Loss In Wag Floodingmentioning
confidence: 99%
“…A 40% reduction in water injectivity index was obselVed. 4 The decrease is attributed to reduced relative permeability to water resulting from a relatively high tmpped N 2 gas satumtion. Further study at the time concluded that the percentage loss in total field injectivity would be substantially less than the loss in well injectivity indices because (1) some wells have excess injection capacity over desired mtes and (2) actual injection mtes into many of the deep wells are controlled primarily by friction pressure losses in the long, 3.5-in [8.9-cm]-diameter tubing strings.…”
Section: Tertiary Performancementioning
confidence: 99%